Experimental assessment of reclaimed bitumen and RAP asphalt mixtures incorporating a developed rejuvenator. (10th August 2019) - Zhang, Jizhe; Sun, Hui; Jiang, Hongguang; Xu, Xiaobin; Liang, Ming; Hou, Yong; Yao, Zhanyong
Highlights: Incorporation of self-designed rejuvenator can improve the colloidal stability of aged bitumen. Self-designed rejuvenator improved the low-temperature cracking resistance of recycled asphalt mixtures. The addition of rejuvenators increased the fatigue life of recycled asphalt mixtures. Abstract: Recycling and reuse of reclaimed asphalt pavement (RAP) in recycled asphalt mixtures is now gaining great interests for sustainability-driven and cost-effective development of asphalt pavements. However, the properties of recycled asphalt mixtures prepared with RAP would be determined by using a suitable rejuvenator to restore original properties of aged (oxidized) bitumen in the RAP. This study investigated the properties of rejuvenated bitumen recovered from RAP as well as the properties of recycled asphalt mixtures prepared with a developed rejuvenator. The properties of the rejuvenated bitumen were evaluated by the SARA (saturates, aromatics, resins and asphaltenes) method, softening point and penetration tests, and the properties of recycled asphalt mixtures prepared with different contents of RAP were determined by wheel tracking, three-point bending (3 PB) and four-point bending (4 PB) tests. Analysis on the conventional properties of the rejuvenated binder showed that the developed rejuvenator can restore the colloidal structure and rheological properties of the aged binder. The incorporation of rejuvenator in recycled asphalt mixtures can decrease the dynamic stability of recycled mixtures, and the maximum bending strain of recycled asphalt mixtures can be increased due to the rheological recovery of the aged binder in the RAP. The fatigue behavior of recycled asphalt mixtures incorporated with the developed rejuvenator was improved as well. Compared to the selected commercial rejuvenator, using the developed rejuvenator can improve more pavement performance of recycled asphalt mixtures.